Faktor-faktor yang mempengaruhi Hasil Kinerja: Komunikasi, Budaya Organisasi dan Sikap - Avriliani Dwi Septiana; Cris Kuntadi (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
Scientific publications and research papers rely heavily on previous research. The goal of previous research and similar search functions is to provide more support for theories and phenomena that focus on interactions between various factors. This article reviews research on organizational behavior and investigates the elements that influence performance outcomes, with a focus on communication, organizational culture, and attitudes. The purpose of this article is to provide a working hypothesis for further study of the interaction of multiple factors. The results of this literature review article are as follows: 1) Communication influences performance results; 2) Organizational culture influences performance results; and 3) Attitudes influence performance results.